Load distribution over threads of planetary roller screw mechanism with pitch deviation. (July 2019) - Zhang, Wenjie; Liu, Geng; Ma, Shangjun; Tong, Ruiting
A model is proposed to calculate load distribution over threads of planetary roller screw mechanism (PRSM) with pitch deviation. Firstly, four kinds of machining errors of threads including pitch deviation, deviation of thread angle, division error of multiple threads and deviation of pitch diameter are analyzed, and the relationships among them are investigated. After analyzing the relationships among the errors, pitch deviation is chosen to be the main machining error to investigate because it can reflect the effects of other machining errors, and is the most influential machining error on the contact condition and deformation compatibility relationship, i.e. the load distribution of PRSM. Based on the proposed model, the effects of pitch deviation on the load distribution of PRSM are studied through numerical analyses, and load distributions under different machining precisions are analyzed. In order to experimentally verify the investigation, two PRSM samples are measured and tested under the same experimental conditions. The experimental results show that load distributions over threads will fluctuate because of the existence of pitch deviations. The pitch deviations, load distributions over threads and wear depths of threads in the samples show obvious accordance, which indirectly demonstrates the effects of pitch deviation on load distribution.